Intellectual humility and political belief bias - Güngör, Mertcan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Intellectual humility (IH) is the tendency to recognize that one’s beliefs may be wrong. The main goals for the first study of this thesis were to replicate and expand upon a previous exploratory finding, IH’s negative relationship with right-wing political orientation, by measuring different aspects of ideology and comparing various perspectives from political psychology literature. IH was not related to political orientation or social conservatism (at least not robustly enough), but it was negatively linked to right-wing authoritarianism. An exploratory analysis also showed that IH was lower in participants who saw ideology as more central for their self-definition. Dogmatism explained both relationships via its negative relationship with IH. The second study aimed to test the validity of an IH scale that was previously adapted to Turkish — General Intellectual Humility Scale — using a syllogism task. Research on syllogistic reasoning has shown that people are affected by the believability of conclusions when evaluating their logical validity; this phenomenon is referred to as belief bias. Contrary to expectations, IH was not negatively related to belief bias. The second study also found that left-wing ideology and analytic thinking were seemingly linked to a reverse belief bias (i.e., participants were more likely to endorse a statement as logically valid when it did not align with their prior beliefs) but these effects disappeared when taking stimulus characteristics into account..
Keywords: Humility.; Thought and thinking.